Rating of muscular and respiratory perceived exertion in professional soccer players - Los Arcos, A.; Yanci, J.; Mendiguchia, J.; Gorostiaga, E. M. (The Journal of Strength and Conditioning Research, 2014)
This study investigated, in male professional players: (a) fluctuations in rating of local-muscular (sRPEmus) and central-respiratory (sRPEres) perceived exertion measured after the completion of each training and competitive session, over a 9-week competitive period and (b) the influence of quantitative assessment of different training and competition modes on changes in physical performance. sRPEres, sRPEmus, and heart rate were measured in 21 players in 847 individual training and competitive sessions. Training load was calculated by multiplying sRPEmus or sRPEres by the duration of the training or competition sessions. A test battery (vertical jump, sprint, and endurance running) was performed before and after the studied period. At the end of official matches, average sRPEmus was higher (7.4 ± 0.6; p < 0.05) than sRPEres (6.4 ± 1.3). Significant negative correlations were observed between the values of total training and competition time (r = -0.62; p < 0.01) or total added sRPEmus (r = -0.59; p < 0.05), and vertical jump or sprint running velocity changes, respectively. This suggests that sRPEmus should be considered the main fatigue rating during a soccer match. Training and competition volume may have negative effects on the muscle power performance gains of the legs.